2020
DOI: 10.1101/2020.11.14.382416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel gene-specific translation mechanism of dysregulated, chronic inflammation reveals promising, multifaceted COVID-19 therapeutics

Abstract: Hyperinflammation and lymphopenia provoked by SARS-CoV-2-activated macrophages contribute to the high mortality of Coronavirus Disease 2019 (COVID-19) patients. Thus, defining host pathways aberrantly activated in patient macrophages is critical for developing effective therapeutics. We discovered that G9a, a histone methyltransferase that is overexpressed in COVID-19 patients with high viral load, activates translation of specific genes that induce hyperinflammation and impairment of T cell function or lympho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…In SARS-CoV-2, trans-nasal and trans-synaptic mechanisms might allow the virus to invade the olfactory bulb and brainstem, with both being the possible initial site for CNS invasion [ 179 ]. Once the virus enters the CNS, it affects neurons, microglia, oligodendrocytes, and especially astrocytes, undermining neurons viability [ 17 , 179 , 180 ].…”
Section: Coronaviruses and Covid-19mentioning
confidence: 99%
“…In SARS-CoV-2, trans-nasal and trans-synaptic mechanisms might allow the virus to invade the olfactory bulb and brainstem, with both being the possible initial site for CNS invasion [ 179 ]. Once the virus enters the CNS, it affects neurons, microglia, oligodendrocytes, and especially astrocytes, undermining neurons viability [ 17 , 179 , 180 ].…”
Section: Coronaviruses and Covid-19mentioning
confidence: 99%
“…The number of neutrophils, macrophages, and lymphocytes were lowered clearly, and the levels of IL-1β, IL-6, and TNF-α in the BALF were decreased, while IL-10 was elevated. Epigenetic changes are linked to lymphocyte movement, as G9a depletion blocks T-cell migration (32), and inhibition of G9a-associated pathways produced systematic mitigation of inflammation and suppression of viral replication (33). These results suggest G9a knockdown repressed inflammation in Spn mice.…”
Section: Discussionmentioning
confidence: 89%
“…Eric Song et.al. found that in the cerebrospinal fluid (CSF) of COVID-19 patients, these activated innate immune cell populations are predicted to interact with CD8 and CD4 T cells applicating CellPhoneDB, suggesting a coordinated anti-viral immunological response occurring in the CSF of COVID-19 patients [ 72 ].…”
Section: Analytical Tools For Ligand-receptor Interactions At Single-cell Levelmentioning
confidence: 99%